Electronic structure and second-order nonlinear optical properties of lemniscular [16]cycloparaphenylene compounds. Issue 24 (7th April 2020) - Gong, Li-jing; Ma, Cheng; Lin, Wan-feng; Lv, Jin-kai; Zhang, Xiang-yu
Abstract : The nonlinear optical property of the studied compounds were studied with the aid of the DFT calculations. Abstract : Chiral organic compounds are excellent second-order nonlinear optical (NLO) materials due to their inherent non-symmetric electronic structures combined with the advantages of organic compounds. At present, density functional theory (DFT) has become a powerful tool for predicting the properties of novel materials. In this paper, based on chiral lemniscular [16]cycloparaphenylene, three novel compounds are designed by introduction of donor/acceptor units and their combinations. The geometrical/electronic structure, electronic absorption, and the second-order NLO properties of these compounds have been systematically investigated by DFT/TDDFT theory. The simulated UV-Vis/CD spectra of compound 1 are in good agreement with the experimental ones, enabling us to assign their electronic transition characteristics and absolute configuration with high confidence. The investigations show that energy gaps, absorption wavelength and second-order NLO response may be effectively tuned by the introduction of the donor or acceptor units or their combinations. For instance, the second-order NLO value of compound 4 is about 207 times as large as the average second-order polarizability of the organic molecule urea. Thus, the studied compounds are expected to be potential large second-order NLO materials.